The role of oil and gas in the development of the global economy - Paul Stevens (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper is concerned with the role of oil and gas in the development of the global economy. Its focus is on the context in which oil and gas producers in both established and developing countries must frame their policies in order to optimize the benefits of producing such resources. It begins by outlining a brief history of the issue over the last 25 years. It considers oil and gas as factor inputs, their role in global trade, the role of oil prices in the macro-economy and the impact of the geopolitics of oil and gas over the same period. The paper then considers various conventional views of the future of oil and gas in the primary energy mix, trying to explain why there is a tendency towards consensus in the different forecasts. Finally, it seeks to challenge these conventional views of the future by examining the various drivers behind them, and to show why the future may prove to be very different from what is expected and how this may change the context in which producers must frame their policy responses.
Keywords: Q40; Q41; Q42; Q43; Q47; Q48; 330; oil; natural gas; energy policy; energy markets